Fish trophic network in karst streams from Brazilian Pantanal headwaters - Severo-Neto, Francisco; Ceron, Karoline; Ceneviva-Bastos, Mônica; Covich, Alan P.; Casatti, Lilian [UNESP] (FapUNIFESP (SciELO), 2024)
Trophic interactions have been a long-standing field of interest in ecology, helping to understand the relationships between organisms and how ecosystems function. In this study, we describe the trophic relationships of fish from karst environments in headwater streams of the upper Paraguai River basin. We analyzed the stomach contents of 81 fish species from the Serra da Bodoquena, calculated the metrics associated with the trophic network, incorporating the body size component in the analyses, and evaluated the participation of each species in network/module connectivity. The analyzed community trophic organization was based mainly on autochthonous items which were the most consumed items for about 30% of fish species. The trophic network showed a modular pattern without nestedness or specialization. However, nestedness was significant within each module, demonstrating a hierarchical compound topology (i.e., species with few connections interacted with subsets of the pairs of more connected species within each module). We also found a relationship between network connectivity and fish body size, in which small species tend to connect modules through generalist feeding strategies. Thus, we demonstrated a still little-known role of small species in fish trophic networks, and how trophic segregation occurs in a highly diverse community from Pantanal headwater streams.
Keywords: Body size; Ecological networks; Serra da Bodoquena; Trophic interactions; Upper Paraguai